Applying ITIL framework to analyze problem management’s KPI: a case study of Mesiniaga Berhad / Abdul Jalil Abdul Rahim - Abdul Rahim, Abdul Jalil (2017)
Problem Management (PM) is one of the components in the Information Technology Infrastructure Library (ITIL) Service Support area. The primary focus of Problem Management is to identify causes of service issues and commission corrective work to prevent recurrences. To address this practice and make it more effective, the project tends to identify the specific Key Performance Indicator (KPI) for Problem Management process in Mesiniaga Berhad. The identification of Problem Management KPI is based on the previous research which is using ITIL as a framework. The interview session has been conducted in Mesiniaga with Problem Manager working at that company with more than 10 years' experience in Problem Management process. The method of interview is using qualitative approach which is using the design question with the lists of KPI. The expert will select or decide which KPI are related with the current report in Mesiniaga. The result showed that 6 KPIs are related and come out with analysis on how the outcome of KPI behaviour matched with the Incident report in Mesiniaga. To enhance on how the identification of KPI, instead of using manual to capture the Problem Management KPI, the automation of selected KPI from Incident to Problem Management can be implement in the systems. Most technology are intelligent enough for data analytic to decide which suitable KPI of Problem Management follow the current business and client environment.